KONFLIK BATIN HANSHIRO TSUGUMO DAN CHIJIWA MOTOME DALAM FILM HARAKIRI: DEATH OF A SAMURAI KARYA TAKASHI MIIKE - Riska Meiwati; Sri Oemiati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2016)
This study examines internal conflict by Hanshiro Tsugumo and Chijiwa Motome. The purpose of this analysis is to know about internal conflict of Chijiwa Motome and Hanshiro Tsugumo. This analysis use data resources â€œHarakiri : Death of a Samuraiâ€ created by Takashi Miike. The problem of internal conflict of Chijiwa Motome and Hanshiro Tsugumo in the HARAKIRI : Death of a Samurai, where analyzed using personality theory including id, ego, superego. In the internal conflict there is a conflict between id and superego which its ego function is unstabil. Based on analysist result that Chijiwa Motome feel internal conflict because he want get a money to fixed his wife and baby, so he did false harakiri in the iyiâ€Ÿs klanâ€Ÿs place. Hanshiro Tsugumoâ€Ÿs internal conflict is his desire to revenge iyiâ€Ÿs klan because of the death of Chijiwa Motome.Keyword: Phsyco analysis, Internal conflict, id, ego, superego